Evaluasi Penafsiran Kelompok LGBT terhadap Makna Kebebasan Hidup dan Kasih - Manase Gulo; Abad Jaya Zega; Oren Siregar; Estherlina Maria Ayawaila; Sarwono Sarwono (JURNAL TERUNA BHAKTI, 2021)
Good and correct interpretation always follows standard and correct hermeneutic principles. Standard and correct hermeneutics is meant to always pay attention to the context and strive for each interpretation result not to conflict with other parts. Based on the results of the researcher's evaluation of the interpretation of the First LGBT people, the term freedom of life according to the 1945 Constitution, especially Article 28 concerning freedom of life, has been mistaken and has even gone astray, because the results presented are contradictory to other articles that have been stated in the 1945 Constitution, For example, the Marriage Law Number 1 Article 1 of 1974, In addition, the LGBT argument is also contrary to Pancasila values and religious values adhered to by religions in Indonesia. The freedom to live in question is the right to live, the right to have an opinion, as long as it does not conflict with the 1945 Constitution and religious values recognized in Indonesia. Christian theology also understands that the freedom a believer has is not the freedom to sin, but freedom from the penalty of sin and the demands of the law. Paul also told the Corinthians that all things are lawful for me, but not all things are useful. Second, the interpretation of love by LGBT people is also mistaken because only seeing and interpreting love is the highest law regardless of the context and the true meaning of love. The behavior of LGBT people is a sin and an abomination in God's eyes. The findings above are the result of an evaluation of the LGBT literature.  AbstrakPenafsiran yang baik dan benar selalu mengikuti kaidah hermeneutik yang baku dan benar. Hermeneutik yang baku dan benar yang dimaksud adalah selalu memperhatikan konteks serta berusaha untuk setiap hasil penafsiran tidak bertentangan dengan bagian-bagian yang lain. Berdasarkan hasil evaluasi peneliti terhadap penafsiran kaum LGBT Pertama, istilah kebebasan hidup menurut UUD 1945 khususnya pasal 28 tentang kebebasan hidup telah mengalami kekeliruan dan bahkan sampai kepada kesesatan berpikir, karena hasil yang dikemukakan bertentangan dengan  pasal-pasal yang lain yang telah dituangkan dalam UUD 1945, misalnya UU pernikahan nomor  1 Pasal 1 tahun 1974, Selain itu, argumentasi LGBT juga bertentangan dengan nilai-nilai pancasila dan nilai-nilai agama yang dianut oleh agama-agama di Indonesia. Kebebasan hidup yang dimaksud adalah berhak untuk hidup, berhak untuk berpendapat, sepanjang tidak bertentangan dengan UUD 1945 dan nilai-nilai agama yang diakui di Indonesia. Teologi Kristen juga memahami bahwa kebebasan yang dimiliki oleh orang percaya bukan kebebasan untuk berbuat dosa, tetapi kebebasan dari hukuman dosa dan tuntutan hukum Taurat. Paulus juga mengemukakan kepada kepada Jemaat di Korintus bahwa segala sesuatu halal bagiku, tetapi tidak semuanya berguna.Kedua, Penafsiran tentang  kasih oleh kaum LGBT juga mengalami kekeliruan karna hanya melihat dan menafsir kasih adalah hukum yang tertinggi tanpa mempedulikan konteks dan makna kasih yang sesungguh. Perilaku kaum LGBT adalah dosa dan merupakan kekejian di mata Tuhan. Hasil temuan di atas merupakan hasi evaluasi literatur kaum LGBT.